Free winds blow west [large type] - Holmes, L. P. (Llewellyn Perry), 1895-1988 (Circle V western., 2016)
From the moment Bruce Martell rode into Indio Basin, he sensed an uneasiness. The cattle showed more than their general wariness at a stranger riding through. Then there were the coyotes and buzzards. Finally, he spotted four beef carcasses that had been slow-elked -- only the choice cuts had been taken, leaving the rest to rot in the sun. Shortly after his arrival, Bruce found himself surrounded by Hank Asbell and his Rocking A cowhands. Asbell didn't suspect Bruce of being involved, but his foreman, Carp Bastion, was of a different mind and an altercation followed. From there Bruce rides into the town of Starlight. Again there is a sense of hostility towards him, this time because he is seen as a man of the saddle as opposed to a man of the plow. As a former frontier lawman, he is aware of the animosity that can grow between cowmen and sod-busters, but even this feels exaggerated. It's not his concern though. He's just here looking for his brother Kip, who had written Bruce that he would be helping a settler and his daughter who were participating in the federally sponsored land rush in Indio Basin. Or so he thinks. Before he knows it, he is drawn into the conflict and will have to draw from his lawman skills to survive.